Professional Lecturer Strategies and Learning Challenges in the Era of Digital Transformation - Umi Imtitsal Rosyidah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
In the era of digital information, this article will discuss how to be a professional lecturer and its challenges in the shift to Industry 4.0. The method used was qualitative-descriptive. The purpose of this descriptive research is to make a description, description or painting systematically, factually and accurately about the facts, characteristics, and relationship between the phenomena being investigated, while the data sources used as references in this study include literature references source from literature-related to the lecturer profession and learning challenges in digital transformation era. Specifically, the government has determined that the strategies and priorities of national education development. The finding also showed that lectures are a profession that must have innovation and creativity because lectures must be able to provide quality teaching, so as to produce students who are unable to think critically. The use of artificial intelligence (AI), is one of the strategies used in technology. It is one of the innovative initiatives that has great potential to change the way to teach in the era of digital information.